Biotherapeutic Potential of Lactobacillus Probiotic Strains on Streptococcus mutans Biofilm in Dental Caries-Pathogenesis Revisited - Vedam, Vaishnavi; Gokul Shankar, Sabesan; Adhikary, Arun Kumar; Parasuraman, Subramani (Indian Journal of Pharmaceutical Education and Research, 2023)
This review gives an insight on the anticariogenic role of each of the individual strains of Lactobacillus probiotics on Streptococcus mutans bacterium associated with dental caries and also attempts to emphasize the commercially approved oral probiotic products using Lactobacillus strains exclusively, against dental caries. Probiotics in bacteriotherapy have been an emerging strategy in the management of ‘Dental caries’. Probiotics, protect the tooth surfaces from the competing microbial pathogens in the mouth. Lactobacillus species despite its acidogenicity has taken a breakthrough in the intervention of dental caries due to its acid buffering capacity with dairy product administration and as late colonizers for dental caries. This article compiled the pathogenesis of individual Lactobacillus strains of probiotics in a well-illustrated manner on S. mutans and also the list of the commercial products of oral probiotics with exclusive lactobacillus strains on S. mutans and its effect on dentistry. Probiotic formulations and recent strategies with future perspectives are emphasized. Also, the role of individual Lactobacillus strains and the associated commercial products against dental caries have been compiled to give additional knowledge regarding the changing strategic approach towards dental caries from the laboratory and clinician point of view. Restorative treatment strategies for dental caries act against both disease causing microbial species and commensal of the oral cavity resulting in undesirable adverse effects. As there is a need to switch to probiotics as a natural therapeutic approach, this review has sheds light on proposed pathogenesis, commercial products and future perspective that will promote researchers to work on new Lactobacillus probiotic formulations with greater efficacy in overcoming the emerging multispecies generating with time in caries.
Keywords: Biofilm; Dental caries; Lactobacillus; Probiotics; Streptococcus mutans